The Impact of Real Earnings Management on Financial Reporting Quality and Its Implications for Investors’ Decisions and Market Efficiency: An Empirical Study of Sumer Commercial Bank for the Period 2016–2025 - Hayder Matloob Koshan; Alyaa Hussein Mohmmed Ali Alesaa; Fawziya Jassoom Kadhim (Indonesian Journal Publisher, 2026)
The research aims to study effect administration Profits the real on quality reports Finance and its reflection on decisions investors and efficiency market Financial, from during study Applied on bank Sumer Commercial For the period Extended From 2016 to 2025. And it stems importance Search from importance Information Accounting in to support decisions investors and strengthening trust in markets Finance, in shadow asylum some Departments to Use practices administration Profits The real To influence in Results Finance Announced and investigation Goals specific It relates By improving Performance Apparent or impact in Prices Shares. Approved. Search on Curriculum Descriptive analytical from during analysis Data Finance and reports Annual Private At the bank, Please on Use group from Methods Statistics To measure relationship between variables Research, Among them coefficient Link and decline Linear. As well. It was completed measurement administration Profits The real from during flows Cash operational not Ordinary, and costs Production not Ordinary, and expenses Optional not Ordinary. And it arrives Search to presence relationship The indication Statistics between practices administration Profits The real Quality Reports Finance, so Leads This is amazing Practices to decrease level Transparency and reliability in Information Finance, Which Reflected negatively on decisions investors and efficiency market Financial . As well . Showed Results that weakness quality Reports Finance leads to to retreat trust investors and increase condition non Confirmation in The market . And recommended. Search Necessity Strengthening role Governance and censorship Interior Foreign Ministry Commitment By standards Disclosure And transparency, and development mechanisms censorship on Practices Accounting To limit from administration Profits The real and improving quality Reports Finance In what Contributes in to lift efficiency market Financial and strengthening trust Investors.